Influência da adição de Zn e Mg nos parâmetros térmicos e microestruturais da liga Al-Sn solidificada unidirecionalmente descendente - Ferreira, Ivanilda Agustinho (2021)
The alloys of the Al-Sn system are used in machine elements, such as plain bearings, which are subject to mechanical stress, allowing the final product low wear. The 1% Sn composition will enable the distribution of Sn particles in the Aluminum matrix and act as a solid lubricant. It becomes necessary to reinforce the matrix rich in Al, therefore, we seek to add third elements, Mg and Zn, which can improve the mechanical behavior. In the literature, studies on thermal parameters and morphology are scarce for the alloys of the ternary Al-Sn- (Mg-Zn) systems, under transient conditions of heat extraction. Microstructural analysis provides complementary information for the analysis of manufacturing processes and affects the properties of materials and their applicability. This study aims to contribute to the understanding of changes in the Al Sn alloy caused by the addition of the composition, 2% Mg and 2% Zn, in the microstructural evolution. The studied alloys Al-1% Sn-2% Mg and Al-1% Sn-2% Zn were subjected to the vertical descending unidirectional solidification process, under transient heat flow regime. Experimental approaches were developed to determine quantitatively the effects of the alloying elements on the thermal solidification variables, such as liquid isotherm velocity (VL) and cooling rate (TR), taking as reference the distance from the cooling camera/metal interface for each position allocated to the thermocouples along the solidified metal ingots. And experimental correlations are proposed between microstructural parameters - interphase spacing (λG), particle diameter (DG), secondary dendritic spacing (λ2) and thermal variables. The results obtained, for the morphology of the alloys in the present study, are characterized by a dendritic microstructure and particles in the form of dispersed globules in the aluminum matrix. The composition of 2% Zn shows lower values of the microstructural parameters (DG, λG, and λ2) for positions closest to the refrigerated base, increasing progressively as the cooling camera / metal interface moves away when compared to the 2% Mg composition. For higher values of VL and TR resulted in structures with particles of smaller diameter and with smaller interphasic and secondary spacing.